Students’ Self Perception Towards Digital Reading: Findings from Indonesian - Syahrir Syahrir; Ainul Fahmi; Andi Muhammad Yusuf (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Digital Reading is one of the options in the context of online learning to stop the Covid-19 virus from spreading since the Covid-19 pandemic has forced schools and colleges to close. The purpose of this study is to describe how students perceptions about learning English using digital reading  when the Covid-19 pandemic is occurring. This study employed a descriptive quantitative methodology. 40 of 6th semester students from English Education Study Program, Guide and Counseling Study Program and Early Childhood Teacher Training Study Program of Universitas Muhammadiyah Palopo, Indonesia were participants. To get data, a questionnaire about student perceptions of the practicality of digital reading was issued as a Google form. According to the study's findings, the majority of students are enthusiastic about the use of digital reading. it is thought to be more helpful and effective in supporting learning activity.